Perspectives of nurses regarding pain assessment and management during routine infant vaccination in Ghana - Emma Annan; Tendani S. Ramukumba; Bonnie J. Stevens (Wiley, 2023)
Abstract Aim To explore the perspectives of nurses regarding pain and its management during routine infant vaccination at the Child Welfare Clinics in Ghana. Design Qualitative descriptive design. Methods Qualitative in depth, in‐person interviews using a semistructured interview guide were conducted with 19 Registered Nurses who were were purposively sampled from three selected Child Welfare Clinics in hospitals in the Greater Accra Region of Ghana, The Tesch cotent analysis procedure was followed for the analysis of interview data. Results Nurses were aware that the injections they give infants are painful. They described how infants exhibit certain behaviours to express pain. Although nurses support infant pain management during vaccination, they rarely use evidenced‐based pain interventions.